Front-End Performance Optimization: A Comprehensive Guide - Narender Reddy Karka (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article explores advanced techniques and best practices for front-end performance optimization in modern web development. The article examines critical aspects of web performance, including Core Web Vitals metrics, render blocking optimization strategies, resource management, and caching implementations. Through analysis of real-world case studies across e-commerce platforms, educational institutions, and content-heavy websites, the article demonstrates the significant impact of performance optimization on user engagement, conversion rates, and business outcomes. The article presents detailed implementation strategies for Critical CSS management, JavaScript optimization, image delivery pipelines, and service worker utilization, supported by code examples and empirical evidence. This article also addresses the growing importance of automated performance monitoring and testing frameworks in maintaining consistent performance standards across web applications.
Keywords: Front-End Performance Optimization; Core Web Vitals; Resource Management; Service Worker Implementation; Performance Monitoring